Establishing a Foreign Exchange Futures Market in China - Jin, Zhongxia; Wang, Haobin; Zhao, Yue. (Washington, D.C. : International Monetary Fund, 2021)
During China's transition toward a more flexible exchange rate, it is essential to further develop its foreign exchange (FX) derivatives markets to meet the growing hedging needs associated with greater exchange rate fluctuations. Although over-the-counter (OTC) FX derivatives markets already exist in China, it lacks a FX futures market that offers critical complementarities. With standardized products, greater transparency and centralized oversight, a FX futures market can better satisfy the hedging needs of small and medium-sized enterprises and enhance regulatory efficiency. To address concerns regarding whether FX futures market will amplify the volatility of spot exchange rates, this paper analyzes the impact of establishing FX futures markets on spot market volatility using data from major emerging market economies. The result shows that FX futures market is not empirically associated with an increase in spot market volatility; in some cases, it is even associated with a decrease in spot market volatility. This paper further suggests that for a well-functioning FX futures market to be established, it is essential for China to substitute the inefficient documentation requirement of underlying exposures with a new set of market-oriented measures for the purpose of prudent regulation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: ADF Test Statistics; Financial Institutions and Services; Foreign Exchange; FX Futures Market, Exchange Rate and Market-Based Regulation; FX Futures Market; International Financial Markets